A Diagnostic study of the civil service in Indonesia. (Metro Manila, Philippines Asian Development Bank, 2020)
Modern civil service must be composed of competent, dedicated, and mission driven public servants to harness opportunities and improve public service delivery with emerging technology. It also needs to proactively adapt and respond to evolving challenges. Based on the civil service size and composition, data on public service delivery, and public opinion, the report identifies improvements necessary to increase the basic competencies of civil servants in the country.
Keywords: Public administration -- Indonesia; Economic development -- Indonesia; Electronic books